Description of a new Patagonian species of Urophonius Pocock (Scorpiones, Bothriuridae), from Meseta de Somuncurá, Argentina - Acosta, Luis E. (Zootaxa, 2003)
Urophonius somuncura n. sp. (Scorpiones, Bothriuridae) is described and illustrated. This species is presumably endemic to the higher plains of the Meseta de Somuncurá (province of Río Negro, Argentina), a basaltic plateau in northern Patagonia. Its nearest relatives are U. granulatus Pocock, from southern Patagonia, and U. tregualemuensis Cekalovic, from central Chile, with all three belonging to the ’granulatus species group’. The diagnostic characters for the new species include the development of the ventral submedian carinae on metasomal segment I, the number of ventral setae on the same segment and presence of tegumentary borders around them, and details of the pigment pattern on carapace, mesosomal tergites and metasoma, among others. U. somuncura n. sp. is seemingly a species active in summer, and its activity period is probably slightly asynchronous in respect to a sympatric Bothriurus species.